PROFESSIONAL AND VALUE ORIENTATIONS OF FUTURE PEDAGOGES OF PRESCHOOL EDUCATIONAL INSTITUTIONS: MODELING OF THE EDUCATIONAL PROCESS IN MODERN INSTITUTIONS OF HIGHER PEDAGOGICAL EDUCATION - Oleksandra Lysenko (Vasyl Stefanyk Precarpathian National University, 2018)
In the article the author presents separate examples of conceptual position that was taken into account during the development and implementation of the experimental stage of the research. His goal was to determine the features and outline ways to update professional-value orientations in higher education institutions. It is proved that an important factor in the regulation and determination of the personality motivational sphere is the formation of students' professional and value orientations. By its content, the professional-value orientation is characterized by a dynamic structure. It is formed by the components presented in the article that ensure the relevance and attractiveness of the values of the pedagogical profession for students, the motivation of their actual behavior and the specifics of the educational activity. The author is guided by the fact that before the beginning of studying, every student should have already formed a hierarchy of pedagogical values in the context of professional orientation under the influence of such a factor as moral values. The article presents some examples of a conceptual position that we have taken into account in the development and implementation of an experimental phase of the study. Purposeful arbitrary activity of the future teacher in which his attitude to the real world of things, people, living conditions, social phenomena is realized are the basis of subjective existence, in particular professional pedagogical activity. From the level of formation of professional-value orientations, dependent success, reliability, productivity, the final result of action (activity), including vocational and pedagogical. Thus, by developing personal qualities, as mentioned above, we directly influence the formation of professional-value orientations and ensure the development of the individual as a whole.The issue of updating professional-value orientations of students appears one of the most important at the present stage. This is evidenced by the state of the problem we have raised in the writings of European and Ukrainian scholars, the availability of multi-dimensional author concepts and approaches to their solution and ways of practical implementation in the real activity of educational institutions of all levels. Key words: professional-value orientations, motivation, future teachers, system-forming components.